2016
DOI: 10.1021/acssuschemeng.6b01605
|View full text |Cite
|
Sign up to set email alerts
|

Efficient DNA-Mediated Electron Transport in Ionic Liquids

Abstract: Engineering, American Chemical Society (ACS). It incorporates referee's comments but changes resulting from the publishing process, such as copyediting, structural formatting, may not be reflected in this document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 77 publications
2
23
0
Order By: Relevance
“…The similar γ values for both double helical structures suggested that the HT mechanisms in A- and B-form duplexes may share common features while mediating hole delocalization over adenine tracts, which was not unexpected due to the fact that only subtle variation on the dynamic motion and stacking structure of the base pairs occurred between the two types of duplexes. In addition to the shallow dependence on bridge length, no apparent oscillatory periods on HT yields were observed, indicating that step-wise hopping mechanism with small domains over adjacent base pairs as the hole carriers may not be dominant in hybrid duplex, similar as in B-form adenine tracts34.…”
Section: Resultsmentioning
confidence: 92%
“…The similar γ values for both double helical structures suggested that the HT mechanisms in A- and B-form duplexes may share common features while mediating hole delocalization over adenine tracts, which was not unexpected due to the fact that only subtle variation on the dynamic motion and stacking structure of the base pairs occurred between the two types of duplexes. In addition to the shallow dependence on bridge length, no apparent oscillatory periods on HT yields were observed, indicating that step-wise hopping mechanism with small domains over adjacent base pairs as the hole carriers may not be dominant in hybrid duplex, similar as in B-form adenine tracts34.…”
Section: Resultsmentioning
confidence: 92%
“…Discotic molecule PyTp and PyTp‐DNA complex are rich in π‐electrons. Furthermore, DNA has been shown to act as a bridge for electron conduction as well ,. The presence of π‐electrons in the medium between electrode and redox species, which is an LB film in the present case, will definitely promote the electron transfer process.…”
Section: Resultsmentioning
confidence: 77%
“…The results suggest that the DNAs complexed with ILs, C 4 mim, are less likely to form folded structure during nanopore analysis possibly due to the increased persistence length of DNA. The binding of ILs to the minor groove of double‐stranded DNA would transform the DNA into more rigid state . The possible conformation of DNA bound with C 4 mim is shown in Figure a.…”
Section: Resultsmentioning
confidence: 97%
“…The binding of ILs to the minor groove of double-stranded DNA would transform the DNA into more rigid state. [25,34] The possible conformation of DNA bound with C 4 mim is shown in Figure 2a. In molecular dynamic (MD) simulation, the bases in DNA strands were reported to be disturbed by the binding of ILs to the minor groove of DNA while the helical structure of double-stranded DNA is well maintained.…”
Section: Resultsmentioning
confidence: 99%